Religiosity-based business performance to increase customer loyalty: Bibliometric Analysis - Triawan, Eko; Asfiah, Nurul (Jurnal Ekuisci, 2025)
This study aims to examine how the influence of religiosity on business performance in increasing customer loyalty. Through a bibliometric analysis approach, this study explores relevant publications regarding the integration of religious values in business strategies and their impact on customer loyalty. Using data from the Scopus database, this analysis identifies research trends, key themes, and significant contributions to understanding the relationship between religiosity and business performance. The results of the analysis show that integrating religious values in business operations not only increases customer trust but also encourages long-term loyalty. This research provides new insights for practitioners and academics in developing business strategies based on religious values to improve company performance and customer loyalty.